Positive Psychology Approach in Islamic Religious Education Learning - Juliati Juliati; Hermawansyah Hermawansyah; Mulyadin Mulyadin (Prodi PAI STIT Sunan Giri Bima, 2026)
This study aims to analyze the application of a positive psychology approach in Islamic Religious Education (PAI) learning as an effort to build psychological well-being and Islamic character in students at SDN 15 Pekat. The study used a qualitative method with a case study design. Data collection was conducted through observation, interviews with the principal, teachers, and students, and documentation. The results of the study indicate that the positive psychology approach is implemented through positive reinforcement, habituation of worship, instilling the values of gratitude, patience, and honesty, and creating a supportive and enjoyable learning environment. The implementation of this approach has a positive impact on increasing self-confidence, optimism, learning motivation, and psychological well-being of students. In addition, this approach also contributes to the formation of Islamic character, such as honesty, discipline, responsibility, empathy, and social concern. The implications of this study emphasize the importance of the role of teachers in consistently integrating the principles of positive psychology with Islamic teachings to create comprehensive and meaningful PAI learning.